Exploring The Qualitative Relationships Between ROA, Financial Distress, Return To Equity Ratio, And Firm Value: A Case Study - Sri Utami Nurhasanah; Sarah Fitriyani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to investigate the intricate relationships among Return on Assets (ROA), Financial Distress, Return to Equity Ratio, and Firm Value within a specific context. Employing a case study approach, the research endeavors to discern the nuanced interplay between these financial metrics. The sampling technique involves purposive sampling to select firms representative of the studied population. Data analysis utilizes qualitative techniques, including thematic analysis and pattern recognition. The findings revealing how ROA, Financial Distress, and Return to Equity Ratio influence Firm Value within the examined context. These insights provide valuable implications for financial management strategies and decision-making processes, particularly in navigating complex financial landscapes.